Fluid Mechanics - Fox, Robert W.; McDonald, Alan T.; Pritchard, Philip J. (Wiley, 2012)
One of the bestselling texts in the field, Introduction to Fluid Mechanics continues to provide students with a balanced and comprehensive approach to mastering critical concepts. The new eighth edition once again incorporates a proven problem solving methodology that will help students develop an orderly plan to finding the right solution. It starts with basic equations, then clearly states assumptions, and finally, relates results to expected physical behavior. Many of the steps involved in analysis are simplified by using Excel